Quo Vadis Objects To Fiduciary Collateral Under Regulations In Indonesia And Malaysia - Budi Susilo (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
means of social engineering where comprehensive laws and regulations can create effective protection of citizens' rights where laws and regulations must keep abreast of developments in the country one of which is a new phenomenon and until now there has been no implementation regulation is copyright which can be used as an object of guarantee fiduciary by looking at the regulations in Indonesia and Malaysia and the issues to be raised are (1) How can a work be used as a fiduciary guarantee in Indonesia and Malaysia (2) What is the comparison between Indonesian and Malaysian copyright regulations In Indonesia, even though it already exists in Article 16 paragraph 3 of Law Number 28 of 2014 , the mechanism for the development of works as a fiduciary guarantee experiences many obstacles, namely regarding the time limit for protection, asset valuation which later refers to Article 40 paragraph (1) while in Malaysia, although in the 1987 copyright deed 332 it is not very clear because it is still in the drafting process by intangible property, where the ownership of Intellectual Property Rights has developed intangible asset-based credit, through the Malaysian Intellectual Property Company (MyIPO) and the Inland Reveneu Board of Malaysia. (LHDN) has provided infrastructure in providing guarantees